Taste receptors affect male reproduction by influencing steroid synthesis - Liu, Wenjiao; Gong, Ting; Shi, Fangxiong; Xu, Houqiang; Chen, Xiang (Frontiers in Cell and Developmental Biology, 2022)
For male genetic materials to reach the egg, spermatozoa must contend with innumerable environmental changes in a complex and highly sophisticated process from generation in the testis, maturation in the epididymis to capacitation and fertilization. Taste is an ancient chemical sense that has an important role in the animal's response to carbohydrates in the external environment and is involved in the body's energy perception. In recent years, numerous studies have confirmed that taste signaling factors (taste receptor family 1, 2 and their downstream molecules, Gα, PLCβ2, et al.) are distributed in testes and epididymis tissues outside the oral cavity, and their functions are related to the processes of spermatogenesis, maturation and fertilization, which are potential targets for regulating male reproduction, but the specific signaling mechanisms are unknown. In this paper, we combine published literature and experimental results from our group (unpublished) to speculate on the signaling mechanism by which taste receptor factors affect male reproduction by influencing testosterone synthesis.